Model Penduga Penentuan Karyawan Teladan Berbasis Adaptive Adaptive Neuro Fuzzy Inference System (ANFIS) - Nico Bustanul Anshary (Universitas Indraprasta PGRI Jakarta, 2017)
PT. Argha Karya is a company engaged in the flexible packaging. The company has not used a particular method, especially fuzzy logic method, to select the best employee. Even though the company is still using a manual calculation system, it has been adopting four criteria for selecting the best employee in a system. Those criteria are years of service, data of attendance, effectiveness of working hours and performance appraisal. Fuzzy logic has more than one method of calculating the estimated result of a particular case. The criteria for selecting the best employee are then processed applying modeling based on Adaptive Neuro Fuzzy Inference System. The process needs training data, testing data and new data. The lowest results of RMSE (Root Mean Square Error) for training data is 1.5092e-06 and for testing data is 2.1437. A decision supporting system for selecting the best employee in the form of GUI (Graphical User Interface) can be made with the help of Matlab software. Then, the established system will be evaluated using SQA (Software Quality Assurance) method. The result of this research shows the Selection of the Best Employee at PT Argha Karya Bogor is objective and the decisions made are more effective and efficient.